When Anointing Becomes Annoying: Remarks on the Polish Supreme Court’s Judgment of 20 September 2013 (II CSK 1/13) - Brzozowski, Wojciech (University of Wroclaw. Faculty of Law, Administration & Economics, 2015)
In the judgment of 20 September 2013 (II CSK 1/13), the Polish Supreme Court ruled in a case that involved a Catholic priest administering the sacrament of anointing of the sick to a non-believer previously put in a drug-induced coma. This case raised much interest among Polish legal scholars but is not widely known abroad, despite the fact that it touches upon key aspects of protection of religious freedom. In fact, it represents a clash of two perceptions of the role of religion in the public sphere and the autonomy of an individual in matters of faith. From the secular perspective, religious freedom has clearly been violated, as the priest’s actions involved interference in the sphere of the patient’s physical and psychological integrity. The religious perspective reverses the columns of the “profit and loss account” of a sacrament administered to a person of a different (or non-existent) religious affiliation: since a withdrawal of pastoral ministry may even deprive such a person of the blessings of eternal life, it is probably better to risk causing short-term psychological discomfort in a person professing a different religion or a non-believer than to expose a believer to the threat of damnation in the name of strictly enforced religious freedom. The aim of the present paper is to examine if the conflict in question could be resolved by way of compromise.
Keywords: ochrona wolności religijnej; autonomia jednostki w sprawach wiary; wyrok Sądu Najwyższego II CSK 1/13